Coatings cerâmicos de alta emissividade como soluções energéticas para fornos industriais - Sako, Eric Yoshimitsu (Universidade Federal de São Carlos, 2021)
Aiming at alternatives to reduce the impacts from the excessive consumption of non-renewable energy sources by the industrial sector, the present work highlights an important technological aspect with the development of innovative high emissivity coatings by using available and low cost refractory precursors, such as spinel (MgAl2O3), titanium oxide (TiO2) and zirconium oxide (ZrO2). High emissivity values (ε = 0.85) were achieved even at high temperatures (1500°C), due to the precise engineering of electronic bands structures, which made the electronic transition mechanism into the major radiation absorption, mainly at the spectrum range associated with the usual temperatures experienced by industrial furnaces. In order to assure that the promising laboratory results would indeed lead to industrial gains, a very reliable emissivity measurement technique was carried out in this thesis and a radiation numeric model was developed by using an open source software which not only attested the actual benefits of such novel coatings, but also introduced new possibilities for simulating high temperature operations. In addition, an extensive database containing the electronic configuration of a vast number of ceramics molecules were evaluated, resulting in the discovery of distinct high emissivity compounds which could be explored for the next generation of low cost and high efficiency materials.
High-emissivity ceramic coatings as energy saving solutions for industrial furnace applications
Keywords: Alta emissividade; Transição eletrônica; Estruturas engenheiradas; High emissivity; Engineered structures; Electronic configuration; Coatings; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS